Women's time use and implications for participation in cacao value chains: evidence from VRAEM, Peru. Issue 7 (3rd October 2019) - Armbruster, Stacy; Solomon, Jennifer; Blare, Trent; Donovan, Jason
ABSTRACT: Bringing inclusion into value chain development requires interventions that account for gender-based constraints and opportunities. Key determinants of women's capacity to participate are their availability and access to interventions. Twenty-four-hour recall surveys with 53 women from households engaged in a cacao expansion intervention in Peru found women with a strong interest in cacao; however, participation was thwarted by household responsibilities and exclusion from training. Findings emphasise the need to actively engage women in intervention design, and monitor and evaluate their time use, recognising the unintended consequences of increased time investments, and hence the unexpected impacts of these development interventions.